Immersive digital storytelling to understand the new learning ecosystem: the revised concentric circles model from both teacher and students’ perspective - Yuan Liu (Smart Learning Environments)
Abstract Design education confronts formidable challenges, which stem partly from the influence of emerging technologies and partly from the inherent characteristics of the design discipline. This discipline is inextricably intertwined with interdisciplinary learning, constructive learning, independent learning, etc. From the teachers’ perspective, this research explores how the learning ecosystem adapts to educational demands under the technological revolution. It also examines how storytelling can be perceived as one essential teaching method. The research is structured into two parts: a questionnaire-based investigation and interviews. Participants are educators from multiple discipline. The results indicate that narrative methods truly can play a more significant role in constructing a learning ecosystem. Moreover, the emergence of new stakeholders such as AI tutors and technical assistance specialists, impacts the formation of reasonable personnel structures in both enterprises and universities. The present study also provides relevant task and tool models to offer more effective application recommendations within the context of teaching directions. Future research will entail a larger sample size, the involvement of more universities across various countries, and the in depth discussions on the ethics of AI-related tools.